Antiracist library and information science : racial justice and community - Black, Kimberly; Mehra, Bharat (Emerald Publishing Limited, 2023)
Antiracist Library and Information Science: Racial Justice and Community presents the scholarship and insights of seasoned academic researchers and experienced practitioners as well as emerging scholars, graduate students, new professionals and activists in the field of LIS on the topic of antiracism. The chapters represent a combination of critical, scholarly and reflective perspectives on the theory, practice and progress made towards the actualization of antiracism in LIS and the creation of racially just communities. This volume has been divided into three main sections. The first section, 'Theoretical Groundings,' addresses the philosophical, ontological, axiological, theoretical and epistemological perspectives on race-based oppression, racial justice and anti-racist values and ethics. The second section, 'Dimensions of the Problem of Race in LIS and Community,' presents explorations of the specific problems of racism in LIS practice - racism embedded in the tools and technologies of the profession and its services, in social relations and in the practices of LIS workplaces. The final section, 'Developing Antiracist LIS and Creating the Beloved Community' presents practical solutions for realizing the vision of an antiracist LIS and the creation of racially justice communities. The contributors have provided a response and initial solutions for how the LIS professions can meet their espoused ideals for providing the best services for their communities. This work provides scholarship, food for thought, frameworks, and proposals for discussions for achieving the end of racism in LIS and the creation of just world.
Keywords: Library science -- Social aspects.; Libraries and minorities.; Anti-racism.; Language Arts & Disciplines -- Library & Information Science -- General.; Community & outreach services.; elektronické knihy; electronic books